Upaya Guru dalam Meningkatkan Motivasi Belajar Siswa saat Pembelajaran Daring pada Mata Pelajaran IPS - Alawiah, Mila; Gusrayani, Diah; Nugraha, Dadan (Jurnal Pena Ilmiah, 2021)
Motivation is an important factor in determining student learning success. The purpose of this study was to find out the efforts made by social studies teachers at SDIT Insan Sejahtera in increasing students' learning motivation during online learning. This study uses a descriptive method through a qualitative approach. The subjects of this study were two teachers in grades IV and V and 10 students in grades IV and V. The instruments used were interview and documentation guidelines. The results of this study indicate that the efforts made by the teacher are to approach before online learning, do ice breaking, use learning media, use appropriate learning methods, use blended learning methods, and use the Quizizz application. Learning outcomes based on student responses after being given some efforts made by teachers in increasing student learning motivation when online learning in social studies subjects received a good and satisfactory response.